South Asian Migrants in United Arab Emirates: Impact and Challenges - Taukeer, Mohammed (Pakistan Journal of Humanities and Social Sciences, 2022)
Present paper is focused on impact of South Asian migrants in the Arabian culture of United Arab Emirates with emerging prospectus and challenges. Major objectives of this research are based on the study of impact of South Asian migrants in the culture of Arab with challenges of identity of South Asian migrants in United Arab Emirates. The field work was conducted in December 2019 in purposively selected cities namely- Dubai and Sharjah in United Arab Emirates. The primary data is collected from 200 South Asian migrants under saturation stage of information under qualitative study design. The primary data is analysed by narratives, descriptions and case study for better interpretation of the findings of the study. The finding of the study shows that there is explicit impact of South Asian culture in United Arab Emirates because there are cordial linkages between South Asian and Arabian culture. These consequences created new cultural landscape included to culture of South Asia and Arabian culture. Additionally, South Asian migrants face socio-economic and political identities among Arabians. Therefore, paper depth analysis the impact of South Asian migrant and their problems in United Arab Emirates with prescribed polices for future research work in the field of impact of South Asian migrants and their problems in Gulf countries.